Utilization of Health Care Facilites at Malino Highland - Adnan, Yudi; Sadarang, Rimawati Aulia Insani; Rusmin, Muhammad (Community Research of Epidemiology (CORE), 2023)
Health is a fundamental right that every citizen in Indonesia has and every level of society has the same right to the health services. This study aims to determine the relationship between geographical factors (distance, travel time and type of transportation) and economic factors, namely the economic ability to reach health services on the utilization of health service facilities in the Malino Highland. This research uses quantitative methods with a cross sectional approach which was carried out in July-August 2023 with a total of 114 heads of household in Dusun Balanglohe, Desa Kanreapia Village, Kecamatan Tombolo Pao, Kabupaten Gowa called Malino Highland. Data collection was carried out through surveys and analyzed bivariately. The research results show that the majority of households have not utilized health services in the last one year. Travel time and type of transportation are related to health service utilization. Meanwhile, distance, income and type of insurance have no relationship with health service utilization. The government and related stakeholders need to develop strategies to increase the accessibility of health services in the Malino highlands area. As a next step, further research can be conducted to explore other factors that may influence health service utilization, such as cultural factors, education, and community perceptions of health services.